Mortality of patients with terminal chronic renal disease in a Huánuco hospital, 2012-2016 - Magariño-Ávalos, Betzabeth L. (2019)
Introduction. Chronic kidney disease (CKD) is considered a global public health problem and constitutes a progressive loss of renal function. In stage 5, known as terminal chronic kidney disease, the patient requires renal replacement therapy (RRT). This work seeks to capture whether the type of dialysis, the type of access and the total time of RRT are related to the mortality of patients with stage 5 CKD of the II-EsSalud hospital in Huánuco. Methods. Observational, analytical, retrospective design of cases and controls. 50 cases and 50 controls were identified. Statistical analyzes were performed through the Chi-2, Odds ratio test with a 95% confidence level. Results. The association between mortality and the risk factors studied was found as: the type of dialysis [P = 0.012; OR = 3.85 (95% CI: 1.27 - 11.63)], the type of access [P = 0.017; OR = 4.04 (95% CI: 1.21-13.43)] and the total time of RRT [P = 0.037; OR = 3.16 (95% CI: 1.03 - 9.68)], and 67.7% of patients were male. It was observed that they were associated with mortality: the age of the patient> 75 years, the male gender, the frequency of more than 3 dialysis per week and the place of origin. Conclusions. There is an association between the type of dialysis, the type of access and the total time of RRT with the mortality of patients with terminal CKD.